Peran Banteng Ambengan Pesanggaran (BANTAS) Dalam Politik Dan Ekonomi Di Desa Pedungan - Jordi, Kadek Ivan; Erawan, I Ketut; Bandiyah, Bandiyah (Jurnal Nawala Politika; 2021: Jurnal Ilmu Politik 2021, 2020)
The figure of the BANTAS organization in improning the economy of their Pedungan village makes it interisting this study with in politics, and being able to take advantage of existing reources. This research used Modular Parties theory by Lucas Martin Novaes to see that brokers act as free agents and the can help to change the support once it’s getting more profitablea. The research method used descriptive qualitative, method using primery data and secondary data, because it describes about the figure of BANTAS in economy and politic. Theresuts of the research are: the first one, where the BANTAS organization change support, because the proposal offered by Kadek Agus Arya Wibawa is more profitable. The second one, the between and social assistant including the informations about job vacancy through Kelian Dinas as the leaders of BANTAS.   Keywords : BANTAS, Political Economic Actor, Pedungan Village